Noah started to solve the equation –4.6p – 6.3p + 3.9 = –9.18 below. Combine like terms: –10.9p + 3.9 = –9.18Apply the next steps to s

Question

Noah started to solve the equation –4.6p – 6.3p + 3.9 = –9.18 below.
Combine like terms: –10.9p + 3.9 = –9.18Apply the next steps to solve the equation. What is the solution?

in progress 0
Kim Chi 2 days 2021-07-22T00:58:57+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-07-22T01:00:27+00:00

    – 4.6 p – 6.3 p + 3.9 = -9.18

    – 10.9 p + 3.9 = – 9.18

    – 10.9 p = – 9.18 – 3.9

    – 10.9 p = – 13.08

    p = ( – 13.08 ) : ( – 10.9 )

    Answer:

    p = 1.2

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )